Políticas de internacionalização da educação superior na região norte do Brasil: uma análise do Programa Ciência Sem Fronteiras na Universidade Federal do Tocantins - Lage, Thelma Silva Rodrigues (Universidade Federal do Tocantins, 2016)
The advent of globalization increasingly imposes the need for knowledge enhancement, making innovation as well as scientific and technological development become established as primary forms of ensuring the participation in the new world order. In this regard, countries around the world attempt to promote changes in their educational systems, inserting themselves into a multifaceted process of higher education diversification, which has been rising especially in the hegemonic centers. The internationalization of higher education arises this way as a central theme in higher education institutions, causing universities strive for expanding their boundaries, aiming not only to boost their nation’s development, but also consolidate ties, in which they will remain imbued with responsibility of providing concrete answers to the society. In this context, Brazilian government presents public policies of internationalization of higher education in order to become part of the international and intercultural dimension of the globalized world by implementing an audacious Program: the Science without Borders. Thus, the purpose of this study is to analyze the mentioned government Program within the northern region of Brazil, highlighting how it has been implemented, especially by the Federal University of Tocantins and verifying in this context, how it has been perceived by its beneficiaries as well as by some managers of the institution. For the development of the dissertation it has been done exploratory and bibliographical research, and it has also been performed the analysis of documents provided by national and international government bodies, from where secondary data that allowed the development of the research were obtained. Furthermore, semi-structured interviews were made, and a hundred and twenty (120) questionnaires were conducted on the beneficiaries of the Program. The results presented in this study showed that the Science without Borders Program has produced significant effects on the furtherance of internationalization of the Federal University of Tocantins, highlighting the participation of low-income students in international academic mobility as well as cultural enrichment of its beneficiaries. However, when viewed from different perspectives within the mentioned institution’s context, the Program exposes weaknesses which point to warning signs deserving of attention, amongst which the inadequate language skill is revealed as the main obstacle to the Program’s success.